ENVIRONMENTAL PARAMETERS AND COASTAL ECOTOURISM POTENTIAL OF AMBON BAY: PARAMETER LINGKUNGAN DAN POTENSI EKOWISATA PANTAI TELUK AMBON - Fredy Leiwakabessy; Viesta Sampe; Muhammad Tarmizi Kubangun (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Ambon Bay is one of the waters in Maluku Province that has the potential for ecotourism, but the quality of the waters needs to be considered because over time it changes and experiences changes to the point of coastal damage from various natural events and human activities, especially on Wayame Village Beach, Galala Village Beach, and Passo Village Beach. This study aimed to determine the environmental parameters of Ambon Bay waters as an ecotourism area. This study measured salinity, pH, dissolved oxygen, temperature, and changes in the coastline using Sentinel 2 Imagery. The results of the study showed that the three locations had DO values ​​of 2.8 mg/L, 3.1 mg/L, and 1.4 mg/L; salinity at 32 ppt, 34 ppt, and 33 ppt; pH ranging from 7.6 to 8.6; and temperatures ranging from 27°C to 29°C, and within a period of 4 years (2018-2022) there have been changes in the coastline. The results of the inventory found several tourist areas that can be revitalized and developed to help the economy of coastal communities. This research can be a reference for village communities and the government in making regulations and activities to prevent damage and handle it appropriately.